Application of the STAD-Type Cooperative Model to Improve Student Learning Outcomes - Heni Yulita; Nazurty Nazurty; Sukendro Sukendro (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study is to determine the improvement in the learning outcomes of mathematical elements through the implementation of a STAD-type cooperative learning model. The research subjects are the students of Class V-A at SDN 1 Sindang Marga, Bayung Lencir District, Musi Banyuasin Regency, for the 2024/2025 academic year. The research objects are the students’ learning activities and their mathematics learning outcomes. Data on the students’ learning activities were collected using observation sheets, while data on their learning outcomes were gathered through achievement tests. The data obtained were subsequently analyzed descriptively and qualitatively. The research findings are as follows: (1) Mathematics learning using the STAD-type cooperative learning model improved the learning outcomes of mathematical elements from Cycle I to Cycle II, and students’ learning activities increased from Cycle I to Cycle II, (2) The learning mastery achieved by the students in Cycle I was 76.47% with a class average score of 78.32, and in Cycle II it increased to 91.18% with a class average score of 86.41; (3) The students’ learning activeness, measured classically, was 65.45% in Cycle I, which increased to 81.82% in Cycle II. Based on these results, and considering the indicators of a fully implemented learning process, it can be concluded that the objectives of this study have been achieved and the formulated action hypothesis is accepted.